Transcatheter Aortic Valve Replacement With the HLT Meridian Valve: Results of the RADIANT Trial. (August 2019) - Rodés-Cabau, Josep; Williams, Mathew R.; Wijeysundera, Harindra C.; Kereiakes, Dean J.; Paradis, Jean-Michel; Staniloae, Cezar; Saric, Muhamed; Radhakrishnan, Sam; Wilson, Robert F.; Kubo, Spencer H.
Abstract : Background: While most self-expanding transcatheter valves are repositionable, only one fully retrievable valve is currently available. The Meridian valve is a new self-expanding valve with full retrievability properties. The objective of our study was to evaluate the early feasibility, preliminary safety, and efficacy of transcatheter aortic valve replacement with the HLT Meridian valve (HLT, Inc). Methods: This was a multicenter early feasibility study including patients with severe aortic stenosis at high surgical risk undergoing transfemoral transcatheter aortic valve replacement with the 25-mm Meridian valve. All serious adverse events were adjudicated by an independent clinical events committee according to Valve Academic Research Consortium-2 criteria. Echocardiography data were assessed by an independent echocardiography core laboratory. Results: A total of 25 patients (mean age, 85±6 years; 80% of men) were included. The valve was successfully implanted in 22 (88%) patients (annulus too large and extreme horizontal aorta in 2 and 1 unsuccessful cases, respectively). Valve retrieval because of an initial nonadequate positioning was attempted and successfully performed in 10 (40%) patients. Echocardiography post-transcatheter aortic valve replacement showed a low mean residual gradient (10±4 mm Hg) and the absence of moderate-severe aortic regurgitation (none-trace and mild aortic regurgitation in 76% and 24% of patients, respectively). Mortality at 30 days was 8%, with no cases of disabling stroke, valve embolization, or major/life-threatening bleeding complications. At 6-month follow-up, the cumulative mortality rate was 12%, with no changes in echocardiographic parameters and no cases of valve dysfunction. The majority of patients (89%) were in New York Heart Association class I-II at 6 months. Conclusions: Transcatheter aortic valve replacement with the Meridian valve was feasible and associated with acceptable early and 6-month clinical results. Valve retrieval after full valve deployment was successfully performed in all attempted cases, and valve performance was excellent, with low residual gradients, no cases of moderate-severe aortic regurgitation, and none-trace residual aortic regurgitation in the majority of patients. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT02838680 (RADIANT-Canada); NCT02799823 (RADIANT-US).